2021
DOI: 10.1007/s00296-021-04975-4
|View full text |Cite
|
Sign up to set email alerts
|

Managing ANCA-associated vasculitis during the COVID-19 pandemic: results from an online survey

Abstract: Management of ANCA-associated vasculitis (AAV) during the COVID-19 pandemic poses unique therapeutic challenges. An online survey was conducted to understand physician’s choices for treating AAV during the COVID-19 pandemic. Web-based survey featuring nineteen questions was circulated amongst physicians across various specialties. The responses regarding immunosuppressive therapy for remission induction and maintenance, COVID-19 testing, and preventive measures were recorded. A total of 304 responses were reco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…To the best of our knowledge, this is the first patient survey designed to assess (1) the changes in medical care provided to vasculitis patients in the COVID-19 pandemic and (2) vaccination acceptance in this patient cohort. While several published reports document the results of surveys that included patients with RMDs, the proportion of vasculitis patients was small and their responses were not analyzed separately; in other studies, only data from the first month of the pandemic were presented (18)(19)(20)(21)(22).…”
Section: Discussionmentioning
confidence: 99%
“…To the best of our knowledge, this is the first patient survey designed to assess (1) the changes in medical care provided to vasculitis patients in the COVID-19 pandemic and (2) vaccination acceptance in this patient cohort. While several published reports document the results of surveys that included patients with RMDs, the proportion of vasculitis patients was small and their responses were not analyzed separately; in other studies, only data from the first month of the pandemic were presented (18)(19)(20)(21)(22).…”
Section: Discussionmentioning
confidence: 99%
“…Endothelial injury and NETosis found in COVID-19 may predispose to small-vessel vasculitis such as AAV [ 29 ]. But in a clinical scenario, it is always difficult to balance the correct amount of immunosuppression and the clinicians might want to err on the side of omission rather than commission, as was evident from a previous survey on this topic [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…Patients with AIRDs are at increased risk of various infections both due to the various immunosuppressive drugs used to control the disease manifestations and due to the immune dysregulation seen in these patients due to underlying AIRD [ 1 ]. Hence the ongoing COVID-19 pandemic has created a great dilemma for clinicians treating various AIRDs, especially life-threatening diseases like anti-neutrophil cytoplasmic antibody (ANCA)-associated vasculitis (AAV) which has been well recognized over past year [ 2 ]. Data from the OpenSAFELY database have shown that the mortality is definitely higher in patients with AIRDs compared to general population [ 3 ].…”
Section: Introductionmentioning
confidence: 99%